2022
DOI: 10.1007/s13311-021-01149-9
|View full text |Cite
|
Sign up to set email alerts
|

EEG Neurofeedback in the Treatment of Adults with Binge-Eating Disorder: a Randomized Controlled Pilot Study

Abstract: Specific alterations in electroencephalography (EEG)-based brain activity have recently been linked to binge-eating disorder (BED), generating interest in treatment options targeting these neuronal processes. This randomized-controlled pilot study examined the effectiveness and feasibility of two EEG neurofeedback paradigms in the reduction of binge eating, eating disorder and general psychopathology, executive functioning, and EEG activity. Adults with BED and overweight (N = 39) were randomly assigned to eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 50 publications
2
13
1
Order By: Relevance
“…RCTs using ILF NF are also lacking in ED, although there are some encouraging results for other forms of NF on this subject, none however address the comorbidity of ED and PTSD. Lackner et al (2016) were able to show significant positive effects of alpha frequency training on several characteristics of disturbed eating behavior and emotional skills in adolescent girls with AN, and recent RCTs have shown the effectiveness of different types of frequency band training and slow cortical potential training in women with subclinical and clinical BED in terms of reducing binge eating episodes (Schmidt and Martin, 2016;Blume et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…RCTs using ILF NF are also lacking in ED, although there are some encouraging results for other forms of NF on this subject, none however address the comorbidity of ED and PTSD. Lackner et al (2016) were able to show significant positive effects of alpha frequency training on several characteristics of disturbed eating behavior and emotional skills in adolescent girls with AN, and recent RCTs have shown the effectiveness of different types of frequency band training and slow cortical potential training in women with subclinical and clinical BED in terms of reducing binge eating episodes (Schmidt and Martin, 2016;Blume et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…NF as a treatment adjunct could further enhance learning experiences (e.g., functional regulation strategies) acquired during traditional treatments (MacDuffie et al, 2018; Unterrainer et al, 2014) and benefit patients through the observation of neuronal changes during psychological treatments (Adcock et al, 2005). Pioneering NF studies indeed showed reductions in binge‐eating or overeating episodes, food cravings, anxiety symptoms, body mass index (BMI), or hunger ratings after food‐specific NF in BED (Blume et al, 2022; Hilbert et al, 2023), individuals with overweight and obesity (Kohl et al, 2019), and restrained eaters (J. Schmidt & Martin, 2015, 2016, 2020). Most of these latter studies used EEG as a well‐established NF technique, which, inter alia, aimed to down‐regulate high beta activity linked to increased food cue awareness.…”
Section: Introductionmentioning
confidence: 99%
“…Both NF paradigms outperformed waitlist (WL) in reducing food cravings ( β = −0.42), anxiety symptoms ( β = 0.47), and BMI ( β = 0.12), but co‐occurring highly favorable changes in WL deserve mention. Of note is that only one third of patients with BED abstained from binge eating after food‐specific EEG‐NF (Blume et al, 2022) and rtfNIRS‐NF (Hilbert et al, 2023) at post‐treatment, but further improvement to ≥50% was found at follow‐up, indicating an apparent variability in NF treatment response. Regarding comparative assessment, rtfNIRS‐NF versus EEG‐NF tended to improve eating disorder psychopathology (EDP), and EEG‐NF versus rtfNIRS‐NF tended to ameliorate general mental health.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, a systematic review on studies using electroencephalography (EEG) revealed increased fronto-central beta activity in individuals with BED and overweight or obesity in resting state and during food cue presentation relative to healthy, normal-weight controls (Blume et al, 2019). These consistent findings initiated the development of brain-directed treatment options which directly target these neural deviations in BED (Imperatori et al, 2018;Blume et al, 2022). EEG-neurofeedback (NF) is such a braindirected treatment approach that seeks to enable individuals to gain voluntary control over their brain functions by providing them real-time feedback on their brain activity (Yucha and Montgomery, 2008), for example via visual stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Building on operant learning, participants are reinforced if they regulate the signal in the desired direction (Sherlin et al, 2011). EEG-NF has shown potential in treating adults with BED (Blume et al, 2022), overweight and obesity (Fattahi et al, 2017;Leong et al, 2018), and subthreshold eating disturbances (Schmidt and Martin, 2015. Specifically, reductions in binge-eating episodes and eating disorder psychopathology were found at post-treatment and at 6-month follow-up of 12 sessions of food-specific EEG-NF, targeting fronto-central high beta activity, or functional near-infrared spectroscopy-based NF, targeting prefrontal cortex upregulation, in a recent randomized-controlled trial for patients with BED (Hilbert et al, 2023).…”
Section: Introductionmentioning
confidence: 99%